Analysis of Fourth-Grade Students' Ability to Express Their Opinions in Elementary Schools - Rozy, Shellawaty M; Sukardi, Sukardi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
Speaking skills are very important for every student, especially in expressing opinions. However, some students are still unable to tell stories and convey their respective opinions. There are several factors influencing it. This study aims to identify the factors that influence the speaking skills of fourth-grade students and their efforts to improve their speaking skills in expressing the opinions of fourth-grade students. This study was carried out in one of the state elementary schools in Pedurungan Kidul 02, Semarang, Central Java. The data collected was qualitative in the form of a narrative about the ability of speaking skills in expressing opinions, the factors that influence speaking skills, and efforts to improve speaking skills in expressing opinions. The data source used was the primary data source and the secondary data source. The data collection techniques were observation, interview, test, and documentation. The results of this study show that: (1) the storytelling ability of the three students of grade four B SD Negeri Pedurungan Kidul 02 Semarang City is still in the low category because students are still unable to retell the stories and are not fluent in expressing their opinions, (2) the factors that influence students speaking skills are the first supporting factors which include models, methods, and learning media as well as linguistic factors and non-linguistic factors. The second factor is inhibiting factors, including physical and psychological conditions. (3) the efforts made to improve students speaking skills are that teachers must modify the use of learning methods, improve facilities and infrastructure, and students must practice a lot to tell stories. The contribution of this research is to create a learning media that can attract students' attention during learning. In addition, modifying or collaborating on learning models and methods used for learning is expected so that students do not feel bored and saturated when participating in learning.